Numerical Solution of Hybrid Fuzzy Mixed Delay Differential Equation by Fourth Order Runge-Kutta Method - Bharathi, D. Prasantha; Jayakumar, T.; Vinoth, S. (Discontinuity, Nonlinearity, and Complexity, 2026)
The hybrid systems are used to study many engineering problems over a period of time. Now, we are adding another parameter called delay to make the hybrid systems to model any biological problems in future. We are extending the system of hybrid fuzzy differential equation to hybrid fuzzy mixed delay differential equation in this research article. The Runge-Kutta method of order four has been used to solve the problem by converting the mixed delay differential equation to multiple retarded delay differential equation. Finally, the numerical example is presented and the results are analyzed.